The Restructuring Righteous Foreign Worker Regulations: The Challenge of Enormous Influx of Foreign Workers - Jaelani, Abdul Kadir; Hanum, Willy Naresta (Unissula, 2024)
Foreign workers are needed to overcome the challenge of a shortage of professional workers. However, the ineffectiveness of foreign worker licensing regulations in Indonesia hampers the supply of qualified foreign workers and impacts regional levy revenues. This research aims to structure the rules for the fair use of foreign workers. This is normative juridical research with conceptual, statutory, and comparative approaches. The results of a comparison of foreign worker regulations in Indonesia and Singapore are used to develop a regulatory concept that is more responsive to the use of foreign workers, especially in the health sector. The idea of licensing law and justice theory is used for analysis. The research results show that the regulations on using foreign workers in Indonesia are not yet comprehensive regarding the rules for qualifying foreign workers as a condition for issuing permits and justifying good public services. The issuance of permits to use foreign workers has been hampered because several regions do not yet have implementing regulations that impact the collection of regional levies. Second, setting up mechanisms for utilizing foreign workers in Singapore is relatively easy and successful with strict digital-based permit requirements. Thus, Indonesia needs to adopt a foreign labor policy system with strict requirements for issuing permits that are accessible in terms of bureaucracy, changes to laws, implementation of regulations, and drafting of regional regulations.